Secure Mobile Transactions Processing System - Bali, Narinder; Mehra, Raghav; Bali, Arvinder (International Journal of Computer Sciences and Engineering, 2025)
Due to the advent of the Internet, electronic business transactions have exploded around the globe. The radical evolution of computers and advancement of technology in the area of hardware (smaller size, weight, low power consumption and cost, high performance) and communications has introduced the notion of mobile computing .Mobile wireless market is increasing by leaps and bounds. Today, new technologies that allow cellular (mobile) phones and other handheld devices to access the Internet have made wireless business transactions possible. This phenomenon is known as mobile commerce or MCommerce. Mobile payments (m-payments) are increasingly being adopted by organisations as a new way of doing business in the 21st century. Recently, more and more people have begun using their mobile phones as a method of payment for online shopping and banking. Mobile payments have become easier than ever. Present security issues of mobiles, payments however, still require improvement. Mobile Commerce is an evolving area of e-commerce, where users can interact with service providers through a mobile and wireless network using mobile device for information retrieval and transaction processing .The challenge for mobile network lie in providing very large footprint of mobile services with high speed and security. Online transactions using mobile devices must ensure high security for user credentials and it should not be possible for misuse. the principal drivers of a resurgent and increased interest in mobile payments. In addition, advances in software and hardware security techniques have made trusted financial transactions possible from these devices. This white paper examines the current state and nature of the mobile payments market, some of the relevant enabling technologies, and looks at the relevant risk, security and assurance issues that security and audit professionals will want to consider when developing and evaluating mobile. Payment services. (TPS) is an information processing system for business transactions involving the collection, modification and retrieval of all transaction data. Characteristics of a TPS include performance, reliability and consistency. TPS is also known as transaction processing or real-time processing